La Ley orgánica de la Universidad de El Salvador - Ellacuría, Ignacio (ECA: Estudios Centroamericanos, 1972)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 27, No. 290, 1972: 749-761.